Efficiency of Capital Budgeting Techniques in Emerging Markets: A Post-Implementation Analysis of Nepalese Manufacturing Firms - Shah, Ghanshyam Prasad; Kumar, Anil (People’s Journal of Management, 2025)
This study examines capital budgeting practices in Nepal's beverage industry, focusing on two representative firms—Sunrise Nepal Food & Beverages Pvt. Ltd. and Birgunj Pure Drinking Water Udyog—to evaluate the efficiency of investment decision-making in emerging markets. Using a mixed-method approach combining financial analysis (NPV, IRR, PBP) and statistical tools, the research compares projected versus actual performance metrics, revealing significant variances: positive discrepancies in Net Cash Outlay (11.46%, 10.38%) and Payback Period (11.49%, 32.68%) indicate cost overruns and delayed recovery, while negative NPV (−9.89%, −33.77%) and IRR (−16.11%, −18.84%) variances reflect profitability shortfalls. Hypothesis testing confirms statistically significant differences for NCO and NPV (p<0.05), highlighting systemic inefficiencies in financial planning. The study contributes novel insights into post-implementation capital budgeting accuracy in developing economies and recommends enhanced financial training, standardized evaluation frameworks, and rigorous post-audits to improve investment outcomes. Findings underscore the critical need for context-adapted capital budgeting tools to bridge theory-practice gaps in Nepal's manufacturing sector.